Familial supravalvular aortic stenosis: a genetic study. Issue 2 (February 1989) - Chiarella, F; Bricarelli, F D; Lupi, G; Bellotti, P; Domenicucci, S; Vecchio, C
Abstract : Supravalvular aortic stenosis (McKusick 18550) is a rare hereditary condition with autosomal dominant transmission. However, the available data have been limited to small family groups which do not allow the definition of the degree of penetrance of the disease. The present study describes a large family with a high frequency of supravalvular aortic stenosis including five generations and 80 subjects, the largest family group with this disease studied so far. The study was carried out prospectively in 66 subjects (clinical examination, ECG, M mode and two dimensional echocardiography). In 14 subjects available data were examined retrospectively. In 10 patients cardiac catheterisation was performed (prospective study in eight). The disease was present in 36 (45%) of the 80 subjects investigated, on the basis of clinical, echocardiographic, and haemodynamic (when available) criteria. The disease was found to be severe in eight cases (22%), moderate in six cases (17%), mild in 13 (36%), and undefined in eight (22%) patients. In one case (3%), multiple pulmonary stenoses were noted in the absence of supravalvular aortic stenosis. Genetic analysis of these data shows, for the first time, the degree of penetrance of the supravalvular aortic stenosis trait (K = 0.86) and confirms that it is transmitted with incomplete penetrance and variable expressivity.